2019
DOI: 10.1177/0739891319833695
|View full text |Cite
|
Sign up to set email alerts
|

Effective Christian Religious Education in Nigerian Secondary Schools as a Mechanism for Sustaining Democracy in Nigeria

Abstract: Nigeria is a nation that is morally and spiritually sick and her democracy is bedeviled with moral, social and political disorders. This article examines the role of Christian religious education in Nigerian secondary schools for the sustenance of democracy. There is a need to emphasize Christian religious education which upholds the principles of peace, non-violence and fair play in politics and elections into offices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies (Tar and Shettima 2010;Salawu and Hassan 2011;Okunoye 2019) showed that Nigeria's pathway towards a peaceful, consolidated, enhanced, and liberal-oriented democracy similar to that of the United States of America was in 1979, where the new constitution created the establishment of a multi-party democracy into the nation's polity and allowed for popular participation. The period of 1979-1983 witnessed the elections under the multi-party arrangement, which saw the emergence of Alhaji Shehu Shagari of the National Party of Nigeria (NPN) under the Second Republic (Isma'ila and Othman 2015; Oluwadunsin Ogunkorode 2019).…”
Section: Historical Context Of the Evolution Of Democracy In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Tar and Shettima 2010;Salawu and Hassan 2011;Okunoye 2019) showed that Nigeria's pathway towards a peaceful, consolidated, enhanced, and liberal-oriented democracy similar to that of the United States of America was in 1979, where the new constitution created the establishment of a multi-party democracy into the nation's polity and allowed for popular participation. The period of 1979-1983 witnessed the elections under the multi-party arrangement, which saw the emergence of Alhaji Shehu Shagari of the National Party of Nigeria (NPN) under the Second Republic (Isma'ila and Othman 2015; Oluwadunsin Ogunkorode 2019).…”
Section: Historical Context Of the Evolution Of Democracy In Nigeriamentioning
confidence: 99%
“…As advocates of social and equal justice that seek to protect the political freedoms and rights of minority, vulnerable, and other marginalized groups, religious groups and its leaders are at the forefront of this crusade and campaign against injustice (Ekeke 2013; Ugwuanyi and Formella 2022). Studies (Ezeanokwasa 2016;Ciftci 2019;Okunoye 2019;Umunakwe et al 2022) revealed that only a secured and consolidated democracy creates the platform and opportunity for these religious groups to advance and carry out their campaigns to check systemic and structural inequalities, poverty, non-inclusion, marginalization, and other forms of discriminatory policies targeted at minorities and other vulnerable members of the community. A respondent supported this line of argument that democracy and peace can succeed in a free, just, religious, and morally sound society.…”
Section: How Does Religion Strengthen Democracy and Peace? The Nigeri...mentioning
confidence: 99%
“…Such education cannot exist without integrity. The need for this kind of education is expressed by Okunoye (2019), in his lament on the moral and spiritual decadence in Nigeria and the role Christian religious education could play. He claimed that there is a need to emphasize Christian religious education that upholds the principles of integrity.…”
Section: A Christian Worldview Answers Philosophical Questions Of Wha...mentioning
confidence: 99%